2010
DOI: 10.1080/15265161.2010.494229
|View full text |Cite
|
Sign up to set email alerts
|

To the Barricades!

Abstract: Mark Rothstein (2010) argues that current American regulations concerning deidentified research data and biological samples, as well as common practice by researchers and researcher overseers, are unethical, as well as quite possibly against the best long-term interests of biomedical research. He's right. Rothstein urges that, as a consequence, A detailed process of public engagement, pilot projects, and careful study is needed before any type of regulatory coverage should be extended to deidentified health in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…The research participant suggested “there has been an over-assumption and a gross expectation of patient altruism” [33]. This kind of reaction fits well with a prediction made by Stanford law professor Hank Greely in 2010: “As more and more people find out what can be done—or is being done—with their health information, their family histories, and their DNA, the pressure for change should grow” [45]. …”
Section: Introductionsupporting
confidence: 53%
“…The research participant suggested “there has been an over-assumption and a gross expectation of patient altruism” [33]. This kind of reaction fits well with a prediction made by Stanford law professor Hank Greely in 2010: “As more and more people find out what can be done—or is being done—with their health information, their family histories, and their DNA, the pressure for change should grow” [45]. …”
Section: Introductionsupporting
confidence: 53%
“…When considering the relation between genomics and stigma, authors seem to locate the potential for stigma in the possibility to attribute genetic risk factors for particular diseases to identifiable population groups (Foster & Sharp, 2006; Goodman, 1996; WHO, 2002). Such an understanding seems to be concordant with views of stigma as a ‘mark’ – an understanding of stigma that has been amply criticised as being overly simplistic (Greely, 2010; Parker & Aggleton, 2003; Phelan, 2005). Moreover, genomic studies tend to focus on complex diseases, for which it is unlikely that any one genetic variant will be identified that could explain disease causation.…”
Section: Introductionmentioning
confidence: 67%
“…As thoughtfully noted by Hank Greely, “As more and more people find out what can be done—or is being done—with their health information, their family histories, and their DNA, the pressure for change should grow” (Greely 2010). …”
Section: Public Perceptions and Public Trustmentioning
confidence: 99%